2021
DOI: 10.1002/jcb.30172
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 induces fibroblasts to release key cytokines involved in pancreatic cell migration

Abstract: Pancreatic ductal adenoma carcinoma (PDAC) is considered one of the deadliest solid cancers as it is usually diagnosed in advanced stages and has a poor response to treatment. The enormous effort made in the last 2 decades in the oncology field has not led to significant progress in improving early diagnosis or therapy for PDAC. The stroma of PDAC plays an active role in tumour initiation and progression and includes immune cells and stromal cells. We previously reported that Bcl2‐associated athanogene (BAG3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It has also been demonstrated recently that BAG3 positive pancreatic stellate cells (PSC) stimulate the release of cytokines such as IL-8, MCP1, TGF-β2, IL-6 that act in a paracrine (on PDAC's) and autocrine manner (on PSC) to alter tumour microenvironment and drive invasiveness and metastasis of pancreatic adenocarcinoma (PDAC) (Yuan et al, 2019). BAG3 also stimulates the secretion of IL-6, chemokine ligand 2 and monocyte chemokine attractant protein from human fibroblasts (HF) present in tumour microenvironment that contributes further to diminished prognosis (Dufrusine et al, 2022). (Stürner & Behl, 2017).…”
Section: Bag3 and Cellular Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated recently that BAG3 positive pancreatic stellate cells (PSC) stimulate the release of cytokines such as IL-8, MCP1, TGF-β2, IL-6 that act in a paracrine (on PDAC's) and autocrine manner (on PSC) to alter tumour microenvironment and drive invasiveness and metastasis of pancreatic adenocarcinoma (PDAC) (Yuan et al, 2019). BAG3 also stimulates the secretion of IL-6, chemokine ligand 2 and monocyte chemokine attractant protein from human fibroblasts (HF) present in tumour microenvironment that contributes further to diminished prognosis (Dufrusine et al, 2022). (Stürner & Behl, 2017).…”
Section: Bag3 and Cellular Metabolismmentioning
confidence: 99%
“…BAG3, particularly its WW domain, has also been found to interact with repressors of the Hippo pathway, leading to the liberation of coactivators in the nucleus (Klimek et al, 2019). Encouraging tumour microenvironment cross‐talk: Recent research has suggested that BAG3 encourages the secretion of proinflammatory cytokines such as IL‐6, IL‐8 and CSF by macrophages, stellate cells and human fibroblasts present in the tumour‐microenvironment (Avinery et al, 2022; Dufrusine et al, 2022; Mantovani et al, 2008; Yuan et al, 2019). These cytokines activate proproliferative, prometastatic pathways, drive further infiltration of macrophages and other cell types and confer chemoresistance thereby contributing to further tumour progression (Rosati et al, 2015).…”
Section: Procancerous Role Of Bag3mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a distinct function was described for secreted BAG3. Indeed, its interaction with IFITM2 (Interferon Induced Transmembrane Protein 2) on the plasma membrane can induce pro-tumoral cytokine release by macrophages [61] and fibroblasts [62], thus sustaining tumor growth. Another relevant protein in this context is the soluble GSTP1 (Glutathione S-Transferase Pi 1), able to catalyze the conjugation of many hydrophobic and electrophilic compounds with reduced glutathione.…”
Section: Termmentioning
confidence: 99%
“…PBMCs were lysed for Western blot analysis, as previously described [178]. Cellular protein amount was determined using the Bradford assay (Bio-Rad, Hercules, CA, USA); cell lysates were denatured in 5X Laemmli sample buffer at 98 • C for 10 min and equal amounts of proteins were separated using 12, 10, or 8% SDS-PAGE and transferred to a PVDF membrane (Merck Millipore, Darmstadt, Germany).…”
Section: Western Blot Analysismentioning
confidence: 99%